2022
DOI: 10.7554/elife.75718
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin signaling in the posterior hypothalamus prevents hyperphagic obesity in mice

Abstract: Decades of studies have revealed molecular and neural circuit bases for body weight homeostasis. Neural hormone oxytocin (Oxt) has received attention in this context because it is produced by neurons in the paraventricular hypothalamic nucleus (PVH), a known output center of hypothalamic regulation of appetite. Oxt has an anorexigenic effect, as shown in human studies, and can mediate satiety signals in rodents. However, the function of Oxt signaling in the physiological regulation of appetite has remained in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…31 The Kublauoui group 32 demonstrated that MC4R agonists activate PVN OXT neurons of WT mice and regulate food intake, indicating that PVN OXT neurons participate in the MC4R neuron feeding circuit. In addition, there are research reports 33,34 that describe the characteristics of a group of small-celled PVN OXT neurons that both responded to and projected to NTS and showed that injection of OVT (an OXT antagonist) into the fourth ventricle attenuated the effect of leptin on food intake. These results support the view that PVN neurons transmit satiety signals to the hindbrain and regulate body weight.…”
Section: Discussionmentioning
confidence: 99%
“…31 The Kublauoui group 32 demonstrated that MC4R agonists activate PVN OXT neurons of WT mice and regulate food intake, indicating that PVN OXT neurons participate in the MC4R neuron feeding circuit. In addition, there are research reports 33,34 that describe the characteristics of a group of small-celled PVN OXT neurons that both responded to and projected to NTS and showed that injection of OVT (an OXT antagonist) into the fourth ventricle attenuated the effect of leptin on food intake. These results support the view that PVN neurons transmit satiety signals to the hindbrain and regulate body weight.…”
Section: Discussionmentioning
confidence: 99%
“…This might provoke an accumulation of unfolded proteins (UPs) and/or additional stress‐related factors, which in turn can be transported to the neighboring neurons through microvesicles, enhancing the cellular stress response by HFD in target neurons (Galluzzi et al, 2018; Pascua‐Maestro et al, 2018). (2) Oxytocin, an anorexigenic peptide, might be induced in response of HFD, and its deletion in the hypothalamus increases food consumption and body weight (Blevins et al, 2016; Castro et al, 2013; Inada et al, 2022; Yoon et al, 2019); therefore, in the Gfap‐Cre , Bmal1 loxP/loxP ‐HFD mice, this pathway might be contributing enhancing the ER‐stress response (Klein et al, 2016). (3) The enhancement of the anti‐stress response in the VMH, might induce the sympathetic BAT activation (Enerback, 2010; Liñares‐Pose et al, 2018; Orozco‐Solis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The central release of oxytocin appears to modulate the motivation to eat by its actions not only in the hypothalamus, but also in the amygdala 33 and at forebrain sites such as the nucleus accumbens 2,34–36 and the ventral tegmental area, 37,38 where it may be involved in food reward. There is also evidence that oxytocin can suppress food intake by its peripheral actions 31,39 …”
Section: Discussionmentioning
confidence: 99%